The importance of nutrition in the life cycle - Agdeppa, Imelda Angeles (World Nutrition Journal, 2024)
Nutrition plays a crucial role from the moment of conception to the final years of life, shaping our health outcomes and improving quality of life. The importance of nutrition in one’s life starts even before birth: during pregnancy, the nutritional status of the mother affects fetal development and pregnancy outcomes. Supplementation of vitamins and minerals is also necessary to ensure optimum fetal growth without compromising the mother’s health.